Modified Endothelial Activation and Stress Index: A New Predictor for Survival Outcomes in Classical Hodgkin Lymphoma Treated with Doxorubicin-Bleomycin-Vinblastine-Dacarbazine-Based Therapy - Fazıl Çağrı Hunutlu; Hikmet Öztop; Vildan Gürsoy; Tuba Ersal; Ezel Elgün; Şeyma Yavuz; Selin İldemir Ekizoğlu; Azim Ali Ekizoğlu; Vildan Özkocaman; Fahir Özkalemkaş (Diagnostics)
Background: Although the cure rates of classical Hodgkin Lymphoma (cHL) are as high as 90% using the current treatment protocols, the prognosis is poor for primary refractory patients. Thus, a biomarker that can predict patients with early progression at the time of diagnosis is an unmet clinical need. Endothelial activation and stress index (EASIX) and its variant modified EASIX (mEASIX) is a scoring system currently used for the prediction of prognosis in hematologic malignancies. This study aimed to investigate the prognostic value of the mEASIX score in newly diagnosed cHL patients. Methods: Data from 206 patients who underwent positron emission tomography (PET)-guided doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) therapy for cHL between January 2007 and November 2023 were retrospectively analyzed. The prognostic value of the mEASIX score was evaluated using the receiver operating characteristic (ROC) analysis, Cox regression analysis, and the Kaplan–Meier method, and then compared with standard risk assessment methods. Results: The median age at diagnosis was 33 years, and the rate of patients in the advanced stage was 67%. ROC analysis determined an optimal mEASIX score cut-off of 17.28, categorizing patients into mEASIXhigh (47%) and mEASIXlow (53%) groups. The 5-year progression-free survival (PFS) (60% vs. 84.3%) and overall survival (OS) (79.6% vs. 95.8%) were significantly lower in the mEASIXhigh group (p < 0.001). Additionally, multivariate analysis showed that the independent variables affecting PFS included the nodular sclerosing subtype (HR: 0.4), bone marrow involvement (HR: 2.6), and elevated mEASIX (HR: 3.1). Independent variables, which had an effect on OS included elevated mEASIX (HR:3.8) and higher IPS-3 scores (HR:1.9). Furthermore, a higher mEASIX score (≥17.28) was identified as an independent variable indicating primary refractory disease (OR: 6.5). Conclusions: mEASIX is a powerful and easy-to-access marker for the detection of primary refractory disease and prognosis in newly diagnosed cHL cases.